Analysis of Energy productivity Decomposition in Iran - Esfandiar jahangard; ali faridzad; jamal kakaie; akbar ahmadi (پژوهش‌های برنامه و توسعه)
The present paper aims to identify the most important factor that explains productivity changes in energy use in Iran over the period of 1385-1394-. Towards this end, the authors have utilized three symmetric industry by industry input-output tables namely, IOT at 1385 constant prices introduced by research center affiliated to Iranian parliament, IOT at 1390 constant prices introduced by Iran’s statistics center and the 1394 -IOT updated by RAS method. Jacob (2003) attribute productivity Changes in energy use to six factors.  The authors have applied the Jacob formula to decompose productivity changes into six cause factors namely, changes in value added, changes in energy consumption, changes in domestic energy supply, structural changes -technology factor, final demand changes, inter industry final demand changes pertaining to agricultural, industry, power, transportation and other service sectors. The results of this study reveal that productivity changes in energy use is negatively affected by value added changes while changes in energy consumption in agriculture and power sectors had a declining impact on productivity and the effect of other factors in productivity changes has been negligible over the period under study.